Effects of Clostridium beijerinckii and Medium Modifications on Acetone–Butanol–Ethanol Production From Switchgrass - Olorunsogbon, Tinuola; Adesanya, Yinka; Atiyeh, Hasan K.; Okonkwo, Christopher Chukwudi; Ujor, Victor Chinomso; Ezeji, Thaddeus Chukwuemeka (Frontiers in Bioengineering and Biotechnology, 2022)
The presence of lignocellulose-derived microbial inhibitory compounds (LDMICs) in lignocellulosic biomass (LB) hydrolysates is a barrier to efficient conversion of LB hydrolysates to fuels and chemicals by fermenting microorganisms. Results from this study provide convincing evidence regarding the effectiveness of metabolically engineered C. beijerinckii NCIMB 8052 for the fermentation of LB-derived hydrolysates to acetone–butanol–ethanol (ABE). The engineered microbial strain (C. beijerinckii_SDR) was produced by the integration of an additional copy of a short-chain dehydrogenase/reductase (SDR) gene (Cbei_3904) into the chromosome of C. beijerinckii NCIMB 8052 wildtype, where it is controlled by the constitutive thiolase promoter. The C. beijerinckii_SDR and C. beijerinckii NCIMB 8052 wildtype were used for comparative fermentation of non-detoxified and detoxified hydrothermolysis-pretreated switchgrass hydrolysates (SHs) with and without (NH4)2CO3 supplementation. In the absence of (NH4)2CO3, fermentation of non-detoxified SH with C. beijerinckii_SDR resulted in the production of 3.13- and 2.25-fold greater quantities of butanol (11.21 g/L) and total ABE (20.24 g/L), respectively, than the 3.58 g/L butanol and 8.98 g/L ABE produced by C. beijerinckii_wildtype. When the non-detoxified SH was supplemented with (NH4)2CO3, concentrations were similar for butanol (9.5 compared with 9.2 g/L) and ABE (14.2 compared with 13.5 g/L) produced by C. beijerinckii_SDR and C. beijerinckii_wildtype, respectively. Furthermore, when C. beijerinckii_SDR and C. beijerinckii_wildtype were cultured in detoxified SH medium, C. beijerinckii_SDR produced 1.11- and 1.18-fold greater quantities of butanol and ABE, respectively, than when there was culturing with C. beijerinckii_wildtype. When the combined results of the present study are considered, conclusions are that the microbial strain and medium modifications of the fermentation milieu resulted in greater production of fuels and chemicals from non-detoxified LB hydrolysates.